A Comparative Study of Porn Use Behavior in Public and Private Schools, Semarang, Indonesia - Datu, Angeline Dayatri Wulan; Mubarokah, Kismi (Jurnal Promosi Kesehatan Indonesia, 2025)
Background: Pornography is one of the factors contributing to the decline in productivity among today's youth. Excessive pornography consumption is an issue among today's youngsters. The widespread consumption of pornography can lead to free sex in today's youth, as well as unplanned pregnancies. The purpose of this study is to compare attitudes, perceptions of behavior control, intentions, and actions related to online pornography consumption in adolescents attending public and private schools in Semarang City.Method: This study used a cross-sectional design with 1,844 stratified random samples. Secondary data from the website http://sehariku.dinus.ac.id comprised participants ranging from junior and senior high school (including vocational schools) to university students. The Mann-Whitney non-parametric test was employed to do a bivariate analysis and compare these variables between the two groups.Result: The findings revealed that the majority of respondents were women (55.4%), in early adolescence (50.6%), and lived with their parents (74.2%). Compared to private schools, public schools had better attitudes (mean rank 937.04), perceptions of behavior control (mean rank 950.37), intents (mean rank 932.73), and behavior (mean rank 927.26). However, no significant difference was found between attitude (p-value 0.129), conduct (p-value 0.584), and intention (p-value 0.288). Only the perceived behavior control variable differed substantially across public and private schools (p=0.004). In this regard, private and public schools are primarily comparable. Some private educational foundations must devise an effective method to increase students' perceived behavior control over pornography, at least to compete with public schools.